Quality of life and oral health impact profile in Turkish dental patients. Issue 3 (September 2016) - Sönmez, Seda; Top, Mehmet
Abstract: Background: OHRQoL, oral health impact assessment and QoL in oral health have become central to dental and oral health research. Researchers studying oral health problems have used OHRQoL as an outcome measure to determine the effect of treatment on QoL in health technology assessment. Aim: Here we aimed to evaluate the effect of oral health related quality of life and oral health impact dimensions on general health related quality of life. Method: Outpatients ( n =527) at a public dental hospital were incorporated into the study. Data were collected using a survey, including questions addressing socio-demographic features, oral health related quality of life (Oral Health Impact Profile-14 [OHIP14] and Oral Health Related Quality of Life – United Kingdom [OHRQoL-UK]) and general health related quality of life (SF-36). Results: We found that OHIP-14, OHRQoL-UK responses significantly correlated with the physical and mental health dimensions of the SF-36. Our data will be useful for health managers and decision makers in health planning and reimbursement policies. Conclusion: The research results are expected to provide important evidence based information to health managers and decision makers in health planning, health technology assessment, and reimbursement policies. Highlights: Clinicians and health managers should analyze quality of life in oral health services. Our study performed that OHRQoL had a significant predictor for HRQoL. Oral health impact on quality of life can be important in oral health policies.